Eye-Specific Projections of Retinogeniculate Axons Are Altered in Albino Mice - Rebsam, Alexandra (Society for Neuroscience, 2012)
The divergence of retinal ganglion cell (RGC) axons into ipsilateral and contralateral projections at the optic chiasm and the subsequent segregation of retinal inputs into eye-specific domains in their target, the dorsal lateral geniculate nucleus (dLGN), are crucial for binocular vision. In albinism, affected individuals exhibit a lack or reduction of pigmentation in the eye and skin, a concomitant reduced ipsilateral projection, and diverse visual defects. Here we investigate how such altered decussation affects eye-specific retinogeniculate targeting in albino mice using the C57BL/6 Tyr (c-2J/c-2J) strain, in which tyrosinase, necessary for melanogenesis, is mutated. In albino mice, fewer RGCs from the ventrotemporal (VT) retina project ipsilaterally, reflected in a decrease in cells expressing ipsilateral markers. In addition, a population of RGCs from the VT retina projects contralaterally and, within the dLGN, their axons cluster into a patch separated from the contralateral termination area. Furthermore, eye-specific segregation is not complete in the albino dLGN and, upon perturbing postnatal retinal activity with epibatidine, the ipsilateral projection fragments and the aberrant contralateral patch disappears. These results suggest that the defects in afferent targeting and activity-dependent refinement in the albino dLGN arise from RGC misspecification together with potential perturbations of early activity patterns in the albino retina.